Development of a beneficiation route to upgrade Sishen iron ore jig slimes for iron making - Molebiemang, G. M. (Vaal University of Technology, 2017)
Kumba Iron Ore’s Sishen mine is located in South Africa’s Northern Cape Province and produces about 40 million tons (Mt) of iron ore per annum. The ore body consists mainly of laminated and massive type hematite ore of which 30 Mt is being beneficiated by Dense Medium Separation (DMS), while the remaining 10 Mt is processed by the jig plant that was added as an expansion to the DMS processing route. The jigs at the jig plant are employed to treat coarse, medium and fine Run of Mine Ore (ROM). Due to the presence of finer particles on the screened ROM, hydrocyclones are employed on the secondary screen that feed the finer jig to produce fines on the overflow that is fed to the thickeners for dewatering by sedimentation, and the formation of clear liquid that can be recycled to the Jig plant. However, it was suspected that a substantial amount of the iron gets lost to the hydrocylone overflow with slimes. These slimes consist of very fine particles (about 90%-45μm) which make treatment with gravity concentration methods difficult. Sishen mine attempts to beneficiate the slimes using Pulsating High Gradient Magnetic Separators (PHGMS). However, PHGMS produce a concentrate consisting of 64.0% iron and 5.0% silica which render the slimes not suitable for pelletizing. Normally the slimes are considered as waste and are rejected to the slimes ponds. Rejecting slimes is not only a loss of resources, but it also poses severe long-term environmental problems. Recovery of iron minerals from the tailings produced in a large iron ore operation is of importance as it will result in environmental and economic benefits which indicate the importance of utilising those accumulated fines.
M. Tech. (Department of Metallurgical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Kumba Iron; Iron mines and mining.; Iron -- Metallurgy.